The role of teacher education in contribution to qualititave improvements in basic education in the developing countries - Bacches, M. Kazim (My University, 1994)
This paper suggests that the increased effectiveness of teacher education programmes in developing countries would help to improve the quality of education offered to students, which could enhance the ability of these countries to survive and even compete more effectively in the emerging global economy. Among the issues discussed in the context of developing countries are: 1) teacher education and the quality of basic education, 2) teacher competence and the declining quality of education, 3) type of teachers needed, 4) increasing the effectiveness of teachers, and 5) prepping teachers for their new role.
Keywords: teacher education